2005
DOI: 10.1111/j.1440-1797.2005.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal cholesterol embolism: Analysis of two spontaneous autopsy cases

Abstract: Two cases of spontaneous cholesterol embolism, which followed different clinical courses, acute and chronic renal failure, are presented and histopathological lesions are compared. Both cases were diagnosed as cholesterol embolism post-mortem. Case 1 (a 66-year-old man) had acute onset of illness with fever, leucocytosis and renal failure, diagnosed as vasculitis, and died of rupture of an abdominal aortic aneurysm. Case 2 (an 84-year-old man) had eosinophilia of unknown aetiology for 7 years with intermittent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…While there have been reported cases in the literature of spontaneous embolisation causing bowel infarction, 3 pulmonary fat embolism, 4 and cerebral infarction, 5 there were no reports on the occurrence of acute renal failure in those instances. Ehara et al 6 did, however, report on two autopsy cases of renal cholesterol embolism in patients who had presented with premortem acute renal failure. Similarly, Tanaka et al 7 found multiple cholesterol embolisation in a postmortem renal sample in a patient who died following presentation with severe hyperreninemic hypertension and renal insuffi ciency.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been reported cases in the literature of spontaneous embolisation causing bowel infarction, 3 pulmonary fat embolism, 4 and cerebral infarction, 5 there were no reports on the occurrence of acute renal failure in those instances. Ehara et al 6 did, however, report on two autopsy cases of renal cholesterol embolism in patients who had presented with premortem acute renal failure. Similarly, Tanaka et al 7 found multiple cholesterol embolisation in a postmortem renal sample in a patient who died following presentation with severe hyperreninemic hypertension and renal insuffi ciency.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most patients studied had severe impairment of renal circulation. These patients carry a poor prognosis, with 1-year mortality rates between 64% and 87%, and monitoring by imaging may certainly help the clinician deal with this complex disease given that angiography is strongly contraindicated both because it is an interventional manoeuvre and because it requires heparin administration [31][32][33]34].…”
Section: Discussionmentioning
confidence: 99%
“…Infatti, nella maggior parte dei pazienti giunti alla nostra osservazione era presente una severa compromissione del circolo renale. Questi sono pazienti a prognosi infausta con mortalità ad 1 anno variabile dal 64% all'87% in cui il monitoraggio strumentale può essere certamente di ausilio al clinico nell'affrontare una così complessa patologia, dal momento che in tali pazienti è fortemente controindicata l'angiografia, sia perché manovra interventistica sia per la somministrazione di eparina [31][32][33]34]. Nella paziente con la middle aortic syndrome l'ECD ha svelato l'alterazione emodinamica a livello renale, giustificando il ricorso a metodiche più panoramiche come l'angio-TC che ha rilevato la complessa situazione anatomica da cui era affetta [22][23][24].…”
Section: Conclusioniunclassified
“…Increased inflammation and eosinophilia may explain the efficacy of corticosteroid treatment reported in several cases. [18,19] Nevertheless, increased mortality with corticosteroid therapy has also been reported. [4] Another point of discussion in the management of CES is the safety and efficacy of anticoagulant and antiplatelet treatments.…”
Section: Case Reportmentioning
confidence: 99%